2019
DOI: 10.1111/are.14424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary starch levels on the growth, plasma metabolites and expression of genes involved in glucose transport and metabolism inPelodiscus sinensisjuveniles

Abstract: Soft-shelled turtle (Pelodiscus sinensis) had become an important aquaculture species in Asian countries, such as China, Japan, Korea and Thailand, due to its high nutritional and medical values (Ip, Lee, Wong,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The range of dietary total phosphorus was designed to be from 1.20% to 3.20% according to the description in the Introduction section. The crude protein (40.80%) and carbohydrate contents (16%) covered nutrient requirements of juvenile Chinese soft-shelled turtle according to previous studies [ 8 , 42 ]. The experimental diets utilized Russian white fishmeal, chicken meal, casein and wheat gluten as dominant protein sources, and used pregelatinized corn starch as the carbohydrate source and fish oil as the lipid source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of dietary total phosphorus was designed to be from 1.20% to 3.20% according to the description in the Introduction section. The crude protein (40.80%) and carbohydrate contents (16%) covered nutrient requirements of juvenile Chinese soft-shelled turtle according to previous studies [ 8 , 42 ]. The experimental diets utilized Russian white fishmeal, chicken meal, casein and wheat gluten as dominant protein sources, and used pregelatinized corn starch as the carbohydrate source and fish oil as the lipid source.…”
Section: Methodsmentioning
confidence: 99%
“…Under the dual pressure of aqueous ecological environment protection and the rapidly increasing price of feedstuffs, there is a desperate need to develop a high-efficiency and environmentally friendly compound feed for this species based on its nutrient requirements. Although some literature exists on its protein, carbohydrate, lipid, vitamins, and mineral requirements [ 5 , 6 , 7 , 8 , 9 , 10 ], little information is available regarding dietary phosphorus requirement of this animal.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study (25) was used to estimate the chemical composition of feed, turtle body, and feces. The contents of plasma glucose (A154-1-1), triglyceride (A110-1-1), total cholesterol (A111-1-1), total amino acid (A026-1-1), lysozyme (A050-1-1), complement 3 (E032-1-1), and IgM (E025-1-1) were determined by the colorimetric method using Flow chart of experimental design.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…The production of Chinese soft-shelled turtle reached ~322,100 tons in 2017 because it is nutritious and delicious [16]. Growing evidences suggested that the requirements of juvenile turtles for lipid, protein, and starch are 6.38%, 42.20%, and 12.73%, respectively [17][18][19]. In terms of the Chinese soft-shelled turtle, substitution of dietary FM with plant protein ingredients including fermented soybean, soy protein concentrates, and rice protein concentrate has yielded positive results [20][21][22].…”
Section: Introductionmentioning
confidence: 99%